2022
DOI: 10.3390/ijms23116174
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Transcriptome Caused by Mutations in the Ribosomal Protein uS10 Associated with a Predisposition to Colorectal Cancer

Abstract: A number of mutations in the RPS20 gene encoding the ribosomal protein uS10 have been found to be associated with a predisposition to hereditary non-polyposis colorectal carcinoma (CRC). We transfected HEK293T cells with constructs carrying the uS10 minigene with mutations identical to those mentioned above and examined the effects of the produced proteins on the cellular transcriptome. We showed that uS10 with mutations p.V50SfsX23 or p.L61EfsX11 cannot be incorporated into 40S ribosomal subunits, while the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…The incidence rate of colorectal cancer(CRC) is the second highest among malignant tumours and the mortality rate is the fourth highest [27] . Since 2016, the incidence rate and mortality rate of CRC have shown an increasing trend.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rate of colorectal cancer(CRC) is the second highest among malignant tumours and the mortality rate is the fourth highest [27] . Since 2016, the incidence rate and mortality rate of CRC have shown an increasing trend.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown how mutant forms of the uS10 protein, resulting from the expression by HEK293T cells of genetic constructs containing copies of the gene encoding uS10 with mutations authentic to those found in patients with a predisposition to CRC, change the cellular transcriptome [ 11 ]. Using RNA-seq and subsequent bioinformatics analysis, we found that among the limited number of genes expressed differentially in the cells generating mutant uS10 forms, there were upregulated genes directly associated with the progression of CRC (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The next-generation sequencing (NGS) of RNA (RNA-seq) is currently an advanced method for studying changes in the transcriptome and translatome landscapes of cells in response to various stimuli, including the deficiency of individual ribosomal proteins [ 23 , 24 , 25 , 26 , 27 ] or the introduction of specific mutations in them [ 28 ]. Being applied to the analysis of total cellular mRNA and mRNAs translated in polysomes, this method makes it possible to draw conclusions concerning the regulation of expression of individual genes at the levels of transcription and translation, and to evaluate their translational efficiencies.…”
Section: Introductionmentioning
confidence: 99%